2007
DOI: 10.12968/bjon.2007.16.4.22993
|View full text |Cite
|
Sign up to set email alerts
|

Transition from paediatric to adult service in epidermolysis bullosa

Abstract: Children with chronic health needs are living longer than they have in the past (Department of Health, 2006) and are becoming adults with complex health needs. This has implications for the health service, which needs to address the arrangements for transfer of young adults from paediatric to adult centres. This article describes the transitional care arrangements established at Great Ormond Street Hospital to address the needs of children with severe epidermolysis bullosa as they move on to adult care. It emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Nearly 10% of the adult patients in our sample population had complex congenital malformations, and one in two patients registered with a diagnosis of inborn errors of metabolism was over 18 years old, which indicates a longer survival than in previous studies [39,40]. We consider these findings of great interest because they have important implications in terms of the need to develop new models of health care provision, like those already adopted for some rare conditions [41-45], which will have to be extended to more and more patients with rare diseases surviving into adulthood [46]. …”
Section: Discussionmentioning
confidence: 81%
“…Nearly 10% of the adult patients in our sample population had complex congenital malformations, and one in two patients registered with a diagnosis of inborn errors of metabolism was over 18 years old, which indicates a longer survival than in previous studies [39,40]. We consider these findings of great interest because they have important implications in terms of the need to develop new models of health care provision, like those already adopted for some rare conditions [41-45], which will have to be extended to more and more patients with rare diseases surviving into adulthood [46]. …”
Section: Discussionmentioning
confidence: 81%
“…Two papers did not correspond with the definitions of palliative care outlined in table 1, and these were: epidermolysis bullosa61 and paediatric illness (empirical) 26. Both highlighted the importance of having transition programs because of the increasing numbers of young people surviving into adulthood and the role of the family in improving the transition process.…”
Section: Resultsmentioning
confidence: 99%
“…Foster and Holmes [26] found that transition for adolescents with epidermolysis bullosa (EB) was facilitated by introducing the process at health care appointments beginning at age 12 with transfer to adult services between the ages of 16–18 years. Recognizing that parents and adolescents have many anxieties related to the transfer, EB nurses attended appointments, made home visits, and visited the adult EB center with the child and parents.…”
Section: Discussionmentioning
confidence: 99%